Epidemiology and risk factors for notifiable Clostridium botulinum infections in Taiwan from 2003 to 2020. Issue 42 (21st October 2022) - Chen, Bao-Chung; Huang, Yao-Ching; Huang, Shi-Hao; Yu, Pi-Ching; Wang, Bing-Long; Lin, Fu-Huang; Chou, Yu-Ching; Hsieh, Chi-Jeng; Yu, Chia-Peng
Abstract : Botulinum toxin is produced by Clostridium botulinum, a gram-positive anaerobic bacterium. This study aimed to examine the epidemiological characteristics, including sex, age, season in which infection occurred, place of residence, and epidemiological trends, of confirmed botulism cases in Taiwan from 2003 to 2020. This study examined the annual summary data on reported botulism in Taiwan' s Center for Disease Control from 2003 to 2020 available to the public on the internet. We found that there were 50 confirmed domestic cases of botulism. The incidence of botulism ranged from 0 to 0.48 per 1000, 000 from 2003 to 2020 and peaked in 2008 and 2010. During the 18-year investigation period in which 6-year intervals were used, the study results showed a decreasing trend (2003–2008, 2009–14, and 2015–2020, had 22, 19, 9 cases each). In terms of patients' gender, age, and place of residence, most of the patients were females (56%), were aged ≥ 50 years (48%), and resided in Taipei and northern Taiwan (44%). The number of botulism cases in Taiwan from 2012 to 2020 compared with other years (from 2003 to 2011) found that there were significant differences among patients within an age group of <20 years ( P = .003, odds ratio = 18.500, and 95% confidence interval = 3.287–104.111), and there were significant differences among patients whose place of residence was Taipei metropolitan area ( P = .025, odds ratio = 5.667, and 95% confidence interval = 1.248–25.734). During 2003 to 2009, there was no case of botulism among those aged <20 years. Over the last 10 years, botulism in children showed an increasing trend. A total of 9 children were found to have botulism during 2010 to 2020; most of these children were male (66.7%) and were infected during spring and summer (66.7%). This study is the first to report the number of confirmed domestic cases with botulism from surveillance data from Taiwan's Center for Disease Control during 2003 to 2020. This study also found that the place of residence and age were associated with an increased risk of botulism in Taiwan. This information may be useful for policymakers and clinical experts to direct prevention- and control-based activities regarding botulism that result in the most severe illness and the greatest burden on Taiwanese.